The Impact of the School Literacy Movement on the Reading Motivation of Junior High School Class Students - Anisah Puteri Djatmiko (PT FORMOSA CENDEKIA GLOBAL, 2022)
Motivation for reading activities in the State of Indonesia in all circles is still minimal, especially students and college students who are also competing in the educational environment. Such incidents have aspects of the problems of the school community, a glimpse of the benefits of literacy. Furthermore, there are also inhibiting factors of a positive culture of active reading. The current generation of government regulations on the subject of positive literacy culture issues a policy of habituating students to reading within 10-15 minutes before the KBM (Teaching and Learning Activities) is carried out. The subject of this research is class VIII students. The findings of the problem formulation in this research event include: 1) What is the influence of GLS in increasing the imposition of students' reading activities? 2) What are the indicative factors that hinder literacy activities? The direction of the problem indicators in this research activity is to be able to find out the impact of the School Literacy Movement (GLS) program on the restructuring of students' reading activities in junior high schools (SMP). This type of research method used is qualitative. The data processing was collected using a brief interview questionnaire accompanied by a description in the form of general knowledge sourced from previous research. The results of this study explained that the indicators of imposition of students' reading activities increased quite a bit